![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
ta có \(\frac{\frac{4}{5}-\frac{4}{11}+\frac{4}{13}}{\frac{9}{5}-\frac{9}{11}+\frac{9}{13}}+\frac{\frac{5}{7}+\frac{5}{11}-\frac{5}{13}}{\frac{9}{7}+\frac{9}{11}-\frac{9}{13}}\)
\(=\frac{4\left(\frac{1}{5}-\frac{1}{11}+\frac{1}{13}\right)}{9\left(\frac{1}{5}-\frac{1}{11}+\frac{1}{13}\right)}+\frac{5\left(\frac{1}{7}+\frac{1}{11}-\frac{1}{13}\right)}{9\left(\frac{1}{7}+\frac{1}{11}-\frac{1}{13}\right)}\)
\(=\frac{4}{9}+\frac{5}{9}=\frac{9}{9}=1\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: =35/11-13/11-7/13-6/13
=2-1=1
b: =2+1/7+6/7+7/9-25/9
=2+1-2=1
c: \(=\dfrac{132}{321}\left(-\dfrac{103}{13}-\dfrac{27}{13}\right)=\dfrac{-132}{321}\cdot10=-\dfrac{440}{107}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,\frac{-1}{9}.\frac{15}{22}.\frac{-9}{25}\)
\(=\frac{-1.15.\left(-9\right)}{9.22.25}\)
\(=\frac{3}{110}\)
\(b,\frac{-2}{7}.\left(\frac{5}{13}-\frac{9}{15}\right)-\frac{2}{7}.\frac{8}{13}\)
\(=\frac{-2}{7}.\left(\frac{5}{13}+\frac{8}{13}-\frac{3}{5}\right)\)
\(=\frac{-2}{7}.\left(1-\frac{3}{5}\right)\)
\(=\frac{-2}{7}.\frac{2}{5}\)
\(=\frac{-4}{35}\)
\(c,\frac{3}{10}.\left(\frac{-4}{9}+\frac{2}{5}\right)-\frac{3}{10}.\left(\frac{5}{9}-\frac{3}{5}\right)\)
\(=\frac{3}{10}.\left[\left(\frac{-4}{9}+\frac{2}{5}\right)-\left(\frac{5}{9}-\frac{3}{5}\right)\right]\)
\(=\frac{3}{10}.\left(\frac{-4}{9}+\frac{2}{5}-\frac{5}{9}+\frac{3}{5}\right)\)
\(=\frac{3}{10}.\left[\left(\frac{-4}{9}-\frac{5}{9}\right)+\left(\frac{2}{5}+\frac{3}{5}\right)\right]\)
\(=\frac{3}{10}.\left(-1+1\right)\)
\(=\frac{3}{10}.0\)
\(=0\)
\(d,\frac{4}{11}-\frac{5}{13}+\frac{7}{11}-\frac{8}{13}\)
\(=\left(\frac{4}{11}+\frac{7}{11}\right)+\left(\frac{-5}{13}-\frac{8}{13}\right)\)
\(=1-1\)
\(=0\)
Học tốt
`2/9 xx7/13+(-11/9)xx 7/13 +7/13`
`=2/9 xx7/13+(-11/9)xx 7/13 +7/13 xx 1`
`= 7/13 xx ( 2/9 + (-11)/9 +1)`
`=7/13xx0`
`=0`
\(\dfrac{2}{9}\times\dfrac{7}{13}+\left(-\dfrac{11}{9}\right)\times\dfrac{7}{13}+\dfrac{7}{13}\)
\(=\dfrac{7}{13}\times\left(\dfrac{2}{9}+\dfrac{-11}{9}+1\right)\)
\(=\dfrac{7}{13}\times0\)
\(=0\)